Nematodiasis in sheep and goats kept under traditional farming practice in Batujajar - ., Beriajaya (Indonesian Journal of Animal and Veterinary Sciences, 2005)
This study was conducted to determine the relation of age, sex, season and reproduction on gastrointestinal nematode parasitism of the two most commonly kept breeds of sheep and goat in Bogor district. A total of 119 Indonesian Thin Tail (ITT) sheep and 130 Peranakan Etawah (PE) goats with different age and sex were monitored for 16 months. Age of sheep and goat was divided into 3 groups respectively, i.e. before weaning (<4 months) 35 and 32, after weaning (4-8 months) 53 and 63; and adults (>8 months) 31 and 35. Each 4 weeks, individual faeces were collected and individual animals were weighed. Information on the mortality, morbidity, pregnancy, slaughtered and sold was recorded. The results showed that Haemonchus contortus and Trichostrongylus spp. were dominant species of nematodes found in the faecal cultured. In the period of monitoring, egg counts of nematodes in sheep were higher (P<0.05) than in goats, however both animals have similar pattern of egg counts. In the first three months, the egg counts remained steady relatively in 3 groups of age, but soon after that the egg counts increased and reached its peak (in March) of 6186 eggs in sheep and 3434 in goats, there after they decreased along with the onset of dry season. A part from this, the egg counts increased (P<0.05) three months before lambing and remained steady until 2 months after partus in sheep, but not in goats. During the monitoring period, weight gain in wet season was lower (P<0.05) as compared to dry season. There was no effect of sex on faecal egg count in either sheep or goats although male sheep had higher egg counts than female sheep had in November and January. Evidence of diarrhoeic faeces was higher in wet season than in dry season. Â  Â  Key Words: Haemonchus contortus, Trichostronglysus spp., Sheep, Goats